2020
DOI: 10.1177/1557988320971917
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Men Into a Pragmatic Rural Primary Care Weight Loss Trial

Abstract: Men remain underrepresented in behavioral weight loss trials and are more difficult to recruit compared to women. We describe recruitment response of men and women into a mixed-gender behavioral weight loss trial conducted within 36 rural primary care clinics. Participants were recruited through primary care clinics via direct mailings ( n = 15,076) and in-clinic referrals by their primary care provider (PCP). Gender differences were examined in response rate to direct mailings, study referral source, and rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…First, participants living further away from their medical clinic may have self‐selected out of the study. However, analysis of participation rates in the trial showed similar rates across clinics randomized to phone visits as for clinics randomized to either individual or group clinic visits, 31 suggesting that required travel to the clinic for counseling visits did not significantly reduce study participation. Second, there is the possibility that some participants may have traveled from their work, not their home, to the clinic.…”
Section: Discussionmentioning
confidence: 95%
“…First, participants living further away from their medical clinic may have self‐selected out of the study. However, analysis of participation rates in the trial showed similar rates across clinics randomized to phone visits as for clinics randomized to either individual or group clinic visits, 31 suggesting that required travel to the clinic for counseling visits did not significantly reduce study participation. Second, there is the possibility that some participants may have traveled from their work, not their home, to the clinic.…”
Section: Discussionmentioning
confidence: 95%
“…This paper characterizes the health of a sample of largely rural dwelling Australians over 65 years of age, a population that has been historically under-researched resulting in minimal evidence to inform health promotion priorities for this age group [ 40 ]. Of most interest was that our population were predominantly male (59%), which addresses important gaps in the evidence as, broadly speaking, males tend to be difficult to recruit in health research, especially in rural areas [ 41 , 42 ]. Overall, most of the population (72.3%) were aged between 66 and 75 years of age and lived in either a large rural (MM3 34.0%) or small rural (MM5 22.3%) town, with lower levels of education (most of our sample reported that they had not completed high school (60.9% of participants)).…”
Section: Discussionmentioning
confidence: 99%
“…The ARFS ranges from 0 to 73, and questions align with foods in the core food groups of The Australian Guide to Healthy Eating [37]. Scores are categorized as "needs work" (<33), "getting there" (33)(34)(35)(36)(37)(38), "excellent" (39)(40)(41)(42)(43)(44)(45)(46), or "outstanding' (47+)".…”
Section: Dietary Intakementioning
confidence: 99%
“…In Australia and internationally, many rural communities face disadvantage due to a multitude of factors, including lack of access to facilities, resources, and services [ 2 ]. Despite a growing international evidence-base for rural weight management program effectiveness [ 9 ], rural men are significantly less likely to take up an offer to participate in mixed-gender programs than women [ 10 ]. The Australian Government’s Men’s Health Strategy highlights the need for interventions that support health in priority population groups, including men in rural and low socioeconomic areas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%